Exploring the water-energy nexus in Brazil: the electricity use for water supply - Nogueira Vilanova, Mateus Ricardo [UNESP]; Perrella Balestieri, Jose Antonio [UNESP] (Elsevier B.V., 2015)
The present work evaluates the electricity use for the water production and supply in Brazil. Five categories of indicators were proposed, that is, per capita, water losses, energy, greenhouse gases (GHGs) and financial/economic, which were used in the definition of municipal average values. It takes an average 0.862 +/- 0.046 kWh m(-3) for production and water supply in the country. The results demonstrate that the water supply systems accounted for, at least, 1.9% of total electricity consumption in Brazil in 2012, and the water loss wastes 27% of water and energy in the water supply systems from Brazil. The production and distribution of 1 m(3) of water in Brazilian cities represents the emission of 0.050 +/- 0.004 kgCO2e, being 0.014 +/- 0.001 kgCO2e.m(-3) associated with the water loss volumes. Furthermore, the average Brazilian cities'expenditure with electricity for the water supply is US$ 0.14 +/- US$ 0.01, which corresponds to 16.8% +/- 0.7% of operating expenditures and 12.9% +/- 0.5% of total expenditure of the WSSs. The NE Region is the one that presents the greatest potential for the application of hydraulic and energy efficiency measures in water supply systems (WSSs). (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Water supply utilities; Water-energy nexus; Electricity consumption